Mature larva of Stenichnus godarti (Latreille) (Coleoptera: Staphylinidae, Scydmaeninae): redescription, hypothesis of displaced epicranial suture and alternative interpretation of homology between chaetotaxic structures - Jałoszyński, Paweł (Zootaxa, 2016)
The mature larva of Stenichnus godarti is redescribed on the basis of a shed larval skin; identification was made by rearing the adult. New data on the life history of St. godarti are provided, including feeding behavior of the larva and adult and longevity of the adult under laboratory conditions. Possible serial homology of chaetotaxic structures across body segments is discussed, and morphological structures of immature St. godarti are compared with those of previously described St. collaris. It is concluded that despite structural similarities and some chaetotaxic structures (mainly on the antennae, mouthparts, legs and thoracic sternites) shared by St. godarti and St. collaris, differences in some important body regions are so profound that it is difficult to draw homologies between setal pattern on the head, thoracic and most of the abdominal tergites, based solely on topological evidence. Differences in the chaetotaxy of the head are especially puzzling and a hypothesis of displaced frontal arms of the epicranial suture is proposed, assuming homology between the presutural setae of St. godarti with postsutural setae of St. collaris. Furthermore, alternative interpretations of dorsal thoracic setae are discussed.